Zmiany ustrojowego kontekstu lokalnej polityki przestrzennej - szanse i zagrożenia - Gorzym-Wilkowski, Waldemar A. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
A new spatial organization and planning act, which means consecutive change of system and legal factors of local spatial policy was appeared in the year of 2003. New legal approaches make stronger the position of local communities governments towards other subjects of spatial organization, increasing therefore chances for rational forming of spatial system. Although this act includes several decisions which can be dangerous for rationality of spatial organization. They are the following: large scale of local plans' graphs, which makes it difficult to produce plans for bigger territories, dependence of plans making and passing on possibility of infrastructure realization by local community and also significant possibilities of realization new buildings independently on local spatial policy established before. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 358-363